Should Unemployment Insurance Be Asset-Tested? - Sebastian Koehne; Nikolas Moritz Kuhn (Institute for the Study of Labor (IZA), 2013)
We study asset-tested unemployment insurance in an incomplete markets model with moral hazard during job search. Asset testing has two counteracting effects on welfare. On the one hand, it improves consumption insurance by introducing state contingent transfers to agents most in need. On the other hand, it worsens the moral hazard problem, since workers have a reduced incentive to save and fewer private resources are used for consumption smoothing during unemployment. Our results show that in a realistically calibrated model of the U.S. economy the two effects nearly offset each other - the optimal rate of asset-testing is approximately zero. This finding is robust to several alternative specifications of the model, including a case with heterogeneous time-discount factors. We conclude that the current U.S. unemployment insurance system is approximately optimal.
Keywords: E21; E24; J65; 330; unemployment insurance; asset-testing; incomplete markets; consumption and saving